2011
DOI: 10.1097/jcp.0b013e3182227e78
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Psychological Impact of Antidepressant-Associated Sexual Dysfunction

Abstract: This study attempted to estimate the prevalence and impact of sexual dysfunction on quality of life, treatment compliance, and dyadic adjustment with spouse. For this, 100 consenting subjects who had history of unipolar depression (as per Mini International Neuropsychiatric Interview) and were in remission (Hamilton Depression Rating Scale, <7) at time of intake and met the selection criteria were recruited. Then, they were assessed on Hamilton Anxiety Scale, Global Assessment of Functioning Scale, Compliance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…[10–13] There is no study available that has specifically evaluated sexual dysfunction in female patients receiving antidepressants.…”
Section: Introductionmentioning
confidence: 99%
“…[10–13] There is no study available that has specifically evaluated sexual dysfunction in female patients receiving antidepressants.…”
Section: Introductionmentioning
confidence: 99%
“…Two Indian studies suggested worse sexual outcome in antidepressant-treated women (relative to men), but neither study used a longitudinal design. 27,28 We found that the proportion of patients who tolerated sexual problems poorly increased from 2.9% at week 2 to 9.8% at week 6. The true value at week 6 could have been as high as 16.3% if data for the 15 patients who dropped out owing to sexual problems had been included.…”
Section: Discussionmentioning
confidence: 80%
“…These findings are comparable to the existing literature. 10,16,13 These findings suggest that the prevalence of sexual dysfunction in various domains and overall prevalence is influenced by the assessment scales and the cutoff used to define sexual dysfunction. In this study, sexual dysfunction was also evaluated by using, a semistructured interview.…”
Section: Discussionmentioning
confidence: 98%